Respuesta :
6 to the second power means 6²
So,
6² ÷ 2 ( 3 ) + 4
=36/2(3)+4
=(18)(3)+4
=54+4
=58
So,
6² ÷ 2 ( 3 ) + 4
=36/2(3)+4
=(18)(3)+4
=54+4
=58
For this case we have the following expression:
"6 to the 2nd power ÷ 2(3) + 4"
Rewriting the expression in algebraic form we have:
[tex] \frac{6^2}{2(3)+4} [/tex]
Rewriting the numerator we have:
[tex] \frac{36}{2(3)+4} [/tex]
Rewriting the denominator we have:
[tex] \frac{36}{6+4} [/tex]
[tex] \frac{36}{10} [/tex]
[tex] \frac{18}{5} [/tex]
Dividing both numbers we have:
[tex]\frac{18}{5} = 3.6[/tex]
Answer:
The result of the given expression is:
[tex]\frac{6^2}{2(3)+4}=3.6[/tex]
"6 to the 2nd power ÷ 2(3) + 4"
Rewriting the expression in algebraic form we have:
[tex] \frac{6^2}{2(3)+4} [/tex]
Rewriting the numerator we have:
[tex] \frac{36}{2(3)+4} [/tex]
Rewriting the denominator we have:
[tex] \frac{36}{6+4} [/tex]
[tex] \frac{36}{10} [/tex]
[tex] \frac{18}{5} [/tex]
Dividing both numbers we have:
[tex]\frac{18}{5} = 3.6[/tex]
Answer:
The result of the given expression is:
[tex]\frac{6^2}{2(3)+4}=3.6[/tex]